A dielectrophoresis-assisted adsorption approach significantly facilitates the removal of cadmium species from wastewater. Issue 2 (11th March 2015) - Hu, Jing; Chen, Huiying; Lan, Bihao; Geng, Junfeng; Li, Hua; Xing, Xuan
<x xml:space="preserve">Abstract</x> A dielectrophoresis-assisted adsorption process, as a novel and efficient technique, is reported for the removal of cadmium species from wastewater.